Collecting Recipes: Byzantine and Jewish Pharmacology in Dialogue - Lehmhaus, Lennart; Martelli, Matteo (De Gruyter, 2017)
Intercultural history of knowledge and science; Late Antique pharmacology/ pharmacotherapy; Talmudic Medicine; Greek medical encyclopedias